The Use of Edmodo to Improve the Writing Ability of English Department Students of State Polytechnic of Padang - Desi Yulastri; Dhini Aulia; Hendro Saptopramono (Politeknik Negeri Padang, 2016)
This study aims to examine the usage of Edmodo for writing 1 subject for English Department students of StatePolytechnic of Padang. The design of this research is experimental design; two classes became the experimental and control groups.There were 25 students in experimental group and 27 students in control group. Edmodo was used in experimental group while thecontrol group was taught without using Edmodo. SPSS program was used to analyse the data. The result showed that theexperimental group had improved significantly in their post test result. The paired samples statistics result showed that the mean ofexperiemental group post test was 70.32, while the control group post test was 63.94. For the t test result, the p value (0.000) was lessthan 0.05 for the experimental group, which means that the null hypothesis was rejected. On the other hand, the p value of the controlgroup (0.06) was greater than 0.05 which means the null hypothesis was retained. From the statistic result, the study has proved thatthe use of Edmodo in writing class can improve students’ writing ability. Therefore, the researchers suggest other lecturers to use thedevice. However, further study may need to involve larger population in order to elucidate further the efficacy of this application.